Firn temperatures 50km upstream of South Pole - Stevens, Christopher Max; Lilien, David; Conway, Howard; Koutnik, Michelle; Waddington, Edwin D.; Fudge, T. J. (U.S. Antarctic Program (USAP) Data Center, 2022)
These data are 6-hourly measurements of temperature in the upper 40 m of firn at a site 50 km upstream of South Pole (89.54 S, 137.04 E). The measurements span the two years from January 2017 to December 2018.